Keterlibatan dan kreativitas dalam pembelajaran terdiferensiasi dengan metode Jigsaw - Gunawan Anggia Rahman; Deni Kurniawan; Dinn Wahyudin; Munir Munir (Curricula: Journal of Curriculum Development, 2026)
Student creativity and engagement in learning activities influence their level of understanding of a learning theory. Elementary school students' interviewing skills pose a challenge in language learning, particularly in classrooms with diverse learning profiles and limited student engagement. To address these pedagogical challenges, this classroom action research examines the effectiveness of integrating differentiated instruction with the Jigsaw Method in improving students' comprehension during interviews. This research was conducted with fourth-grade students who exhibited heterogeneous levels of understanding and creativity, necessitating adaptive and collaborative learning strategies. A quantitative approach was used, utilizing interview comprehension tests, creativity observations, and student engagement questionnaires as data sources. Data were analyzed using correlational and regression techniques to identify relationships between variables and the impact of learning. The results showed that integrating differentiated instruction and the Jigsaw Method effectively improved students' comprehension during interviews. Adaptive, collaborative, and contextually designed learning can support students' optimal comprehension during interviews.